PENGARUH KOMITMEN ORGANISASI DAN KEAKTIFAN SISWA TERHADAP MINAT BELAJAR SISWA DI SMA NEGERI 3 BABELAN - DEDE HENDARDI (ACADEMIA: Jurnal Inovasi Riset Akademik, 2021)
The purpose of this study was to determine: 1) The effect of organizational commitment on student interest in learning at SMA Negeri 3 Babelan for the academic year 2020/2021. 2) The effect of student activity on student interest in SMA Negeri 3 Babelan for the 2020/2021 academic year. 3) The effect of organizational commitment and student activity on student interest in learning at SMA Negeri 3 Babelan for the academic year 2020/2021. This research belongs to the type of quantitative descriptive research with conclusions drawn through statistical analysis. The population in this study were OSIS administrators and extracurricular members of SMA Negeri 3 Babelan for the 2020/2021 academic year. Samples were taken as many as 90 students with random sampling technique. The required data was obtained through questionnaires and documentation. The previous questionnaire was tested and tested for validity and tested for reliability. The conclusions of this study are 1) There is a significant effect of organizational commitment (X1) on students' interest in learning (Y). This is based on multiple linear regression analysis (t test) it is known that tcount > ttable, which is 3.883 > 1.66 and the significance value = 0.05. 2) There is a significant effect of student activity (X2) on student interest in learning (Y). This is based on multiple linear regression analysis (t test) it is known that tcount > ttable, which is 4.021 > 1.66 and the significance value = 0.05. 3) There is a simultaneous significant effect of organizational commitment (X1) and student activity (X2) on students' interest in learning (Y). This is based on multiple linear regression analysis (t test) it is known that tcount > ttable, which is 19.888 > 3.10 and the significance value = 0.05. ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui: 1) Pengaruh komitmen organisasi terhadap minat belajar siswa SMA Negeri 3 Babelan tahun ajaran 2020/2021. 2) Pengaruh keaktifan siswa terhadap minat belajar siswa SMA Negeri 3 Babelan tahun ajaran 2020/2021. 3) Pengaruh komitmen organisasi dan keaktifan siswa terhadap minat belajar siswa SMA Negeri 3 Babelan tahun ajaran 2020/2021. Penelitian ini termasuk jenis penelitian deskriptif kuantitatif dengan penarikan kesimpulan melalui analisis statistik. Populasi dalam penelitian ini adalah pengurus OSIS dan Anggota ekskul SMA Negeri 3 Babelan tahun ajaran 2020/2021. Sampel diambil sebanyak 90 orang siswa dengan teknik random sampling. Data yang diperlukan diperoleh melalui angket dan dokumentasi. Angket sebelumnya diuji cobakan dan diuji validitas serta diuji reliabilitas. Kesimpulan dari penelitian ini adalah 1) Terdapat pengaruh yang signifikan komitmen organisasi (X1) terhadap minat belajar siswa (Y). Hal ini berdasarkan analisis regresi linier ganda (uji t) diketahui bahwa thitung > ttabel, yaitu 3,883 > 1,66 dan nilai signifikansi ? = 0,05. 2) Terdapat pengaruh yang signifikan keaktifan siswa (X2) terhadap minat belajar siswa (Y). Hal ini berdasarkan analisis regresi linier ganda (uji t) diketahui bahwa thitung > ttabel, yaitu 4,021 > 1,66 dan nilai signifikansi ? = 0,05. 3) Terdapat pengaruh yang signifikan secara simultan komitmen organisasi (X1) dan keaktifan siswa (X2) terhadap minat belajar siswa (Y). Hal ini berdasarkan analisis regresi linier ganda (uji t) diketahui bahwa thitung > ttabel, yaitu 19,888 > 3,10 dan nilai signifikansi ? = 0,05.